2021
DOI: 10.1177/13621688211046351
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ practices of proactive and reactive classroom management strategies and the relationship to their self-efficacy

Abstract: Teachers’ proactive and reactive classroom management strategies are a significant component of teaching effectiveness. Teachers need to develop such strategies to structure a positive classroom environment. In addition, teachers’ self-efficacy beliefs concerning their classroom management strategies are equally significant. This research aimed to identify the teachers’ effective proactive and reactive classroom management strategies. It also sought to investigate the obstacles that inhibit proactive classroom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…These findings show that EFL instructors self-report themselves as "high" on their self-perceived self-efficacy in classroom management and teaching; however, they also believe that the effect of external factors is effective in classroom management. The findings of a more recent study by Yüner and Barış Pekmezci (2021) showed that instructors who reported themselves as high on selfefficacy also rated themselves high on their classroom management skills, which exacerbates previous research (Alasmari & Althaqafi, 2021). This is likely because instructors' self-efficacy beliefs are based on what they perceive regarding their abilities in classroom management rather than what they actually perform in their classrooms (Aliakbari & Heidarzadi, 2015;Bandura, 1997;İnceçay & Keşli Dollar, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…These findings show that EFL instructors self-report themselves as "high" on their self-perceived self-efficacy in classroom management and teaching; however, they also believe that the effect of external factors is effective in classroom management. The findings of a more recent study by Yüner and Barış Pekmezci (2021) showed that instructors who reported themselves as high on selfefficacy also rated themselves high on their classroom management skills, which exacerbates previous research (Alasmari & Althaqafi, 2021). This is likely because instructors' self-efficacy beliefs are based on what they perceive regarding their abilities in classroom management rather than what they actually perform in their classrooms (Aliakbari & Heidarzadi, 2015;Bandura, 1997;İnceçay & Keşli Dollar, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…This approach therefore suggests that teacher performance-going beyond the transmission of knowledge -will depend on the teacher's ability to perceive and interpret classroom events that are relevant to students' learning and to decide how to adjust his/her performance to manage them strategically. Proactive strategies are essential for maintaining a positive and conducive learning atmosphere, and they align with the ecological perspective by addressing the root causes of behaviour within the classroom ecosystem (Alasmari and Althaqafi 2021).…”
Section: Classroom Management From An Ecological Perspectivementioning
confidence: 99%
“…According to the World Bank (2020), disruptions resulted in significant curriculum learning losses, changes to teaching methodologies and routines, high learner and teacher absenteeism and increase in learner drop-out rates. These teaching and learning disruptions had a significant impact on learner well-being and behaviour (Alasmari & Althaqafi, 2021). South Africa is an example of a country that supports and mandatorily implements proactive behaviour management.…”
Section: Literature Reviewmentioning
confidence: 99%